Musical understandings and other essays on the philosophy of music - Davies, Stephen, 1950- (Oxford : Oxford University Press, 2011)
'Musical Understandings' presents an engaging collection of essays by Stephen Davies on the philosophy of music. He explores a range of topics, including how music expresses emotion, modes of perception, and musical profundity. The volume includes original material, newly revised articles, and work published in English for the first time.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Music -- Philosoophy and aesthetics